Editorial - Pasierbek, Wit (Horyzonty Wychowania, 2017)
Since 1989 the transformation of the post-communist Europe has been referred to as building civic society in particular countries, connected with regaining independence, recreating a sovereign state, rebuilding political community and, above all, making the citizen sensitive to responsibility for the society and common good. The fifty years of totalitarianism in Poland caused that the society, to a large degree, lost the sense of responsibility for the things which constituted and still constitute common property of the nation many generations. Since the time of political changes, the time has come for a serious reflection upon the broadly-understood education in the sphere of social life, for considering the things which make the society live, as well as its aspirations and desires. Therefore, we shall also reflect on how this community perceives its common good and how it wants this good to be realised.